684 Exposure from gun smoke activates several systemic inflammatory pathways. (24th April 2018) - Kongerud, J; Borander, AK; Voie, Ø; Øvstebø, R; Longva, K; Alexis, NE; Ueland, T; Sikkeland, LIB
Abstract : Introduction: Norwegian Armed Forces reported episodes of acute respiratory symptoms after exposure to fumes from firing small arms weapon HK416 (Heckler and Koch) using unleaded ammunition. These fumes contain a mixture of gases and solid particles, that may be capable of inducing inflammatory immune responses. The aim of the present study was to find out if exposure to fumes from small arms could induce systemic and airway inflammation, and whether there were any differences between the ammunition types (leaded, and two types of unleaded). Methods: Fifty-five healthy men (age 19–62) were recruited and randomised to three groups using HK416 and one of the three types of ammunition. Spirometry and collection of blood and sputum samples were performed 2–4 days before shooting, and 1.5 hour (spirometry), 24 hour (blood and spirometry) and 48 hour (sputum) after shooting under standardised conditions. Exposure was monitored. Results: All subjects had a significant increase in median sputum and blood neutrophils (sputum: 46% to 73%, p<0.001; blood: 2.9 × 10 6 /mL to 7.1 × 10 6 /mL, p<0.001). CRP was significantly elevated from 1.3 mg/L to 18.5 mg/L (p<0.001) along with other markers of systemic inflammation (PTX3, YKL-40, SpD, CC16, CXCL16, vWF, MPO, CD25, CD14). CRP and number of neutrophils in blood had a larger increase with unleaded as compared to leaded ammunition. For the whole group, mean FEV1 and FVC decreased 290 mL (p<0.001) and 130 mL (p<0.001), respectively. Discussion: All subjects displayed elevated airway and in particular systemic inflammation following the use of small arms. The changes in systemic markers were enhanced acute stress response (CRP, PTX3), immune cell upregulation (sCD25, sCD14) and increased vascular inflammation (MPO, vWF, CXL16, YKL40). Increased airway inflammation was present at 48 hour post exposure and was accompanied by reduced spirometry that appeared <1.5 hour and lasted >24 hour after exposure. These results suggest that soldiers may be at increased risk to inflammation-based disorders when repeatedly using small arms.